In vitro Relative Fitness, in vivo Intestinal Colonization and Genomic Differences of Escherichia coli of ST131 Carrying blaCTX–M–15 - Hertz, Frederik Boëtius; Marvig, Rasmus L.; Frimodt-Møller, Niels; Nielsen, Karen Leth (Frontiers in Microbiology, 2022)
Introduction Extended-spectrum beta-lactamase (ESBL) producing Escherichia coli have become prevalent worldwide, with E. coli of sequence type 131 (ST131) as the dominant genotype. E. coli ST131 predominantly exhibits the serotype O25, is associated with the ESBL CTX-M-15 and belongs to a well-defined subclade within the FimH30-R clade, FimH30-Rx/C2. Multidrug resistance may have fitness costs for the bacteria. The aim of the current study was to investigate the fitness burden compared to a susceptible ST131 isolate without resistance genes in vitro and in vivo and describe genetic differences between fit and less fit isolates. Materials and methods From a collection of clinical ESBL and non-ESBL E. coli isolates from urinary tract infection, we selected 16 blaCTX–M–15-positive isolates of ST131. The in vitro fitness was examined, and relative bacterial fitness (fitt) was determined by direct competition with a fully susceptible ST131 isolate and illustrated in percent, with <100% resulting in a lower fitness, compared to the susceptible reference isolate. The isolates were subjected to whole-genome sequencing and analyzed for resistance markers, plasmids, phage content, and serotype. In vivo competition was tested in a mouse colonization model. Results The majority (12 out of 16) of the CTX-M-15-producing isolates had a slightly lower relative fitness compared to the susceptible ST131 isolate (mean, 97.6%; range, 82.6–108%) in vitro. Three isolates had a better fitness than the susceptible ST131 isolate, and one isolate had an identical fitness to the susceptible ST131 isolate. The in vitro fitness showed no correlation to the number of plasmids, number of phages, number of resistances, or genome size. For the in vivo competition assays, all three ESBL-producing isolates showed better colonization of the ESBL-resistant ST131 isolates compared to the susceptible ST131 isolate. Conclusion This study shows that ESBL-producing ST131/H30-Rx are not necessarily burdened by multidrug resistance, however, have a better in vitro fitness than the susceptible isolate. These data contribute to the understanding of the success of ST131/H30-Rx, although they do not indicate ways to overcome this highly fit, virulent, and antimicrobial-resistant clone.